APLIKASI PENJUALAN ONLINE SPARE PART MESIN ALAT BERAT DI PT. BUDI JAYA AGUNG - Masagus Muhammad Yusuf (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
Sale of Spare parts of heavy equipment business is subject to the PT Budi Jaya Agung. But until now .PT. Budi Jaya Agung is still making sales manually assisted with the distribution of brochures to the Member. Therefore at the end of this project will be implemented in application development of heavy equipment spare part using the web based PHP and MySQL as database systems dreamweaver 8 the design view of the web online. The purpose of the construction of the application heavy equipment spare part web-based media is expected to be a liaison between corporate managers and members who need information, and can extend the reach of marketing to promote the product. The results of the application of this form of web-based sales data report the member purchase. Keywords : Sales , Online , PHP MySQL , Web , Dreamweaver